Research Progress in Tumor Diagnosis Based on Raman Spectroscopy - Wang, Zhichao; Shi, Huanghao; Zhou, Litao; Yin, Jian; Yin, Huancai; Xie, Liangxu; Chang, Shan (Current Medical Imaging, 2024)
Background Cancer is a major disease that threatens human life and health. Raman spectroscopy can provide an effective detection method. Objective The study aimed to introduce the application of Raman spectroscopy to tumor detection. We have introduced the current mainstream Raman spectroscopy technology and related application research. Methods This article has first introduced the grim situation of malignant tumors in the world. The advantages of tumor diagnosis based on Raman spectroscopy have also been analyzed. Secondly, various Raman spectroscopy techniques applied in the medical field are introduced. Several studies on the application of Raman spectroscopy to tumors in different parts of the human body are discussed. Then the advantages of combining deep learning with Raman spectroscopy in the diagnosis of tumors are discussed. Finally, the related problems of tumor diagnosis methods based on Raman spectroscopy are pointed out. This may provide useful clues for future work. Conclusion Raman spectroscopy can be an effective method for diagnosing tumors. Moreover, Raman spectroscopy diagnosis combined with deep learning can provide more convenient and accurate detection results.
Keywords: Tumor